An LCA comparison of last-mile distribution logistics scenarios in Milan and Turin municipalities. Issue 1 (March 2021) - Croci, Edoardo; Donelli, Matteo; Colelli, Francesco
Highlights: The environmental footprint of last mile-logistic operations is assessed via an LCA. Substituting diesel vehicles with electric vehicles is associated with a positive life-cycle environmental impact. Electric vehicles reduce by 40% to 50% global warming and photochemical smog formation related impacts. Electric vehicles reduce by 15% to 25% acidification related impacts. Particulate matter emissions are reduced only if electric vans are coupled to renewables' generation. Abstract: The paper assesses the environmental footprint of last-mile distribution logistics operations through the application of a life cycle analysis method (LCA). The environmental impacts of the delivery activities carried out in the Limited Traffic Zones (LTZ) of the cities of Milan and Turin by a large private logistics operator are quantified. Through a scenario analysis, current delivery practices and an alternative solution, consisting of replacing the diesel vehicle fleet with electric vehicles (EV), are evaluated. The following environmental impact categories are considered: climate change; particulate matter caused by emission of inorganic substances; photochemical smog formation; acidification. The results show that, compared to current delivery methods, the adoption of EV is associated with an environmental impact reduction between −40% and −50% for global warming and photochemical smog formation, and a reduction between −15% and −25% for acidification. The adoption of the EVs increases the particulate matter emissions compared to diesel vehicles (by up to + 13%) due to the carbon intensity of the national power system, while it reduces them by −7% when at least 50% of the electricity is sourced from dedicated photovoltaic columns.